1995
DOI: 10.1111/j.1440-1754.1995.tb00856.x
|View full text |Cite
|
Sign up to set email alerts
|

Changing patterns of survival and outcome at 4 years of children who weighed 500–999 g at birth

Abstract: The advances in neonatal intensive care for extremely low birthweight infants between July 1977 and December 1982 and January 1983-June 1988 resulted in an increased number of non-disabled survivors but had no impact on incidence of severe disability. The application of prediction of mortality or severe handicap to clinical practice has the potential to reduce the proportion and absolute number of severely handicapped survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 21 publications
1
14
0
1
Order By: Relevance
“…In a similar hospital based study Tudehope et al produced much the same findings 11. A 20 year population based study in Norway showed a fall in CP rates, overall, and also for VLBW infants despite a 50% reduction in perinatal mortality in all weight groups 12.…”
Section: Discussionmentioning
confidence: 70%
“…In a similar hospital based study Tudehope et al produced much the same findings 11. A 20 year population based study in Norway showed a fall in CP rates, overall, and also for VLBW infants despite a 50% reduction in perinatal mortality in all weight groups 12.…”
Section: Discussionmentioning
confidence: 70%
“…The substantial improvement in survival among very preterm infants is well documented. [6][7][8] While questions have been raised about aggressive care for very preterm infants because of potentially increasing disability rates, evidence suggests that disability rates among survivors has remained constant. 1,2,7,9,10 However, as more and more very preterm infants survive, the overall population prevalence of major disabilities should increase.…”
Section: Discussionmentioning
confidence: 99%
“…1±12 Some studies of infants born in the 1980s report decreasing rates of disability over time, 11 whereas others have found no improvement in outcome of extremely low birthweight or preterm infants. 12 Hack et al 13 found that at school age babies born weighing less than 750 g in the mid-1980s in Ohio were more at risk of neurobehavioural dysfunction and school performance problems than children born weighing 750±1499 g or at full term.…”
Section: Introductionmentioning
confidence: 99%